PREVENTION AND ADJUVANT TREATMENT OF ACUTE RESPIRATORY DISEASES OF CHILDREN AND ADULTS WITH BIOPTRON-PILER-LIGHT - Gulyar, S. A. (Medical Informatics and Engineering, 2020)
Background. The review contains brief information on new aspects of physiotherapy (photobiomodulation) using polarized light of the Bioptron device. The palette of its active biophysical components includes 12 types of poly- and monochromatic light from halogen and LED sources. Their anti-inflammatory, analgesic, reparative, immune-normalizing, antimicrobial and other efficacy have been proven experimentally and clinically. Among the main indications are also various types of pathology of the skin and mucous membranes, treatment of wounds and the consequences of injuries, optimization of rehabilitation processes and other conditions subject to physiotherapy treatment. Materials and methods. Results. Additional specific therapeutic possibilities arise due to the creation of monochromatic (quasilaser) ranges, light modifications with fullerene with toroidal polarization and an extended range with the addition of near-ultraviolet light. PILER-light acts both locally on cells and photosensitive molecules, normalizing the electromagnetic balance in them, and systemically through influence on blood structures and acupuncture points. The bactericidal and antiviral efficacy of BIOPTRON light has been experimentally proven. During the cold season, non-invasive prophylaxis and treatment of colds with the help of BIOPTRON light therapy is essential to reduce negative manifestations without pharmacological burden on the body. The protocols for the prevention and treatment of acute respiratory diseases have been tested. Among personal protective equipment, it is advisable to reduce the light load and create mechanical obstacles to protect the eyes by using glasses with fullerene Alters. Conclusions. The main feature of ZEPTER technologies as a whole is their health-saving essence, realized through multilevel antioxidant protection. All this is a necessary component of the measures used in case of acute respiratory diseases.